Post activation potentation response of male vs. female collegiate badminton athletes - Manuel, Vincent Rafael G. (College of Human Kinetics, University of the Philippines Diliman, 2019)
The aim of this study is to test if sex is a factor in post-activation potentiation response (PAP). To test for PAP response, twenty male (n=10) and female (n=10) collegiate badminton athletes underwent two protocols: weight training protocol(1 set, 5 repetitions of 5-RM trap bar deadlift) and control (no intervention) protocol. To test for leg power, the countermovement jump height will be measured using an inexpensive, portable approach named My Jump 2 App which uses the leg length subtracted by the height of the knees and ankles prior to take-off was used. A paired t-test will be used to compare the control versus the PAP protocol in each group while the difference between the post and pre-jumps will be tested using an independent t-test. Significant differences were then analyzed using Cohen's d. The level of significance will be set at the p<0.05 level. The paired T-tests have shown that there is a significant increase for the males in the control (p=0.007) and PAP protocol (p=0.001) while there were insignificant increases in both the control (p=0.061) and PAP protocol (p=0.172) for the females. The independent t-test showed that the response of PAP was significantly better for the males (p=0.019). In conclusion, a warm-up regime involving trap bar deadlifts with the same protocol may be used for short-term improvements for males but not for females. Therefore, it can be suggested that PAP response is more favorable for males as compared to females.